Review of Eziwho Emenike Azunwo’s The Last Don - Abosede, Adetunji Mary; Azunwo, Eziwho Emenike (Journal of Gender and Power, 2024)
Publishers International LTD is a powerful and thought-provoking play that delves into the pervasive issue of sexual abuse within Nigerian tertiary institutions. Set against the backdrop of Academia, the play serves as a critical examination of the socio-cultural, economic, and political realities that define contemporary Nigerian society. Azunwo’s work not only highlights the systemic failures that allow such abuses to persist but also calls for a collective awakening to the urgent need for reform and justice.